Leadership and nurses' satisfaction with supervision. - Melo, Rosa Cândida de Carvalho Pereira de (2015)
Objective: The main objectives of this study were to evaluate the performance of leadership roles and the nurses' satisfaction with supervision and to examine the relationship between the performance of leadership roles and nurse satisfaction. Methods: A quantitative, descriptive, correlational and transversal study was conducted, with a sample made up of 79 nurses practicing in two public health institutions in the district of Coimbra in Portugal. Data collected included demographic characteristics, eight leadership roles and ï¬ÂÂÂve levels of supervision satisfaction. The Munson's Supervision Satisfaction Scale and the Quinn's Leadership Scale were used. The instruments adaptation and validation study revealed adequate psychometric properties being considered as valid instruments for the quantitative study pursuance. Results: The results indicate an acknowledgement of all roles of leadership, having a tendency towards the roles of producer (4.73) and director (4.64) indicating leadership centered on the rational goals model, revealing a greater concern with efï¬ÂÂÂciency and productivity. The role of innovator was the one least perceived (4.16). Most nurses (83.50%) were satisï¬ÂÂÂed with the supervision. The relationships between all the leadership roles and nurse satisfaction were positive, with the roles of facilitator (r = .842; p < .001) and mentor (r = .871; p < .001) with the strongest correlation. Conclusions: The investigation revealed that the leader who plays all roles of leadership raises the level of supervision satisfaction of the nurses he/she leads. A poor performance of the facilitator role suggests the need for head nurses to acquire leadership skills which help them manage interpersonal conï¬‚icts and promote cohesion and teamwork within the current context of health care restructuring and decreased nurse stafï¬ÂÂÂng levels.